2020
DOI: 10.2196/16228
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptability and Usability of Digital Health Interventions for Adults With Depression, Anxiety, and Somatoform Disorders: Qualitative Systematic Review and Meta-Synthesis

Abstract: Background The prevalence of mental health disorders continues to rise, with almost 4% of the world population having an anxiety disorder and almost 3.5% having depression in 2017. Despite the high prevalence, only one-third of people with depression or anxiety receive treatment. Over the last decade, the use of digital health interventions (DHIs) has risen rapidly as a means of accessing mental health care and continues to increase. Although … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
100
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 51 publications
17
100
1
2
Order By: Relevance
“…Positive attitudes are associated with an increased likelihood of behaviour and behavioural intentions (Davis, 1989;Fishbein & Ajzen, 1975;McEachan, Conner, Taylor, & Lawton, 2011;Rosenstock, Strecher, & Becker, 1988). Such as in the case of DI, people with more favourable attitudes to DI are more likely to have positive intentions to use DI, and this is supported by research (Askari, 2020;Patel et al, 2020;Wangberg, Gammon, & Spitznogle, 2007). Therefore, people's attitudes are crucial to understanding people's readiness to engage with DI.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Positive attitudes are associated with an increased likelihood of behaviour and behavioural intentions (Davis, 1989;Fishbein & Ajzen, 1975;McEachan, Conner, Taylor, & Lawton, 2011;Rosenstock, Strecher, & Becker, 1988). Such as in the case of DI, people with more favourable attitudes to DI are more likely to have positive intentions to use DI, and this is supported by research (Askari, 2020;Patel et al, 2020;Wangberg, Gammon, & Spitznogle, 2007). Therefore, people's attitudes are crucial to understanding people's readiness to engage with DI.…”
Section: Introductionmentioning
confidence: 97%
“…It is also essential to consider what shapes these attitudes to DI to provide insight into how people come to have these attitudes and potential avenues of modification. Several factors shape people's attitudes to DI including knowledge (Mayer et al, 2019), confidence using DI (Davis, 1989(Davis, , 1993 and perceptions of accessibility (Patel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has published a systematic review and meta-synthesis of qualitative data on enrollment and retention in the study or treatment from 24 trials of digital interventions with varying degrees of human engagement in enrollment, follow-up, or treatment of people with depression and anxiety. It identified that enrollment and retention to studies were determined by the participants’ initial beliefs about digital health interventions, the offer of personal support, and the enablement of personalization of care [ 52 ]. Taking our results together with this meta-synthesis, the public health campaign and automated enrollment only provided a superficial understanding of what was being offered by the trial.…”
Section: Discussionmentioning
confidence: 99%
“…Also, qualitative studies focusing on knowledge gain and usage in ICBT are very rare. A meta-synthesis identified 24 studies reporting qualitative data about adult clients' experiences of digital health interventions (Patel et al, 2020). They found three key themes revealing the experienced value of personalizing treatment content to the unique individual, how pre-intervention beliefs such as hope can affect participant engagement, and the importance of receiving personal support in order to understand and engage with the program properly.…”
Section: Measuring Knowledge In Icbtmentioning
confidence: 99%